Distinct Functions for Mammalian CLASP1 and -2 During Neurite and Axon Elongation - Sayas, Carmen Laura; Basu, Sreya; van der Reijden, Michael; Bustos-Morán, Eugenio; Liz, Marcia; Sousa, Monica; van IJcken, Wilfred F. J.; Avila, Jesus; Galjart, Niels (Frontiers in Cellular Neuroscience, 2019)
Mammalian cytoplasmic linker associated protein 1 and -2 (CLASP1 and -2) are microtubule (MT) plus-end tracking proteins that selectively stabilize MTs at the edge of cells and that promote MT nucleation and growth at the Golgi, thereby sustaining cell polarity. In vitro analysis has shown that CLASPs are MT growth promoting factors. To date, a single CLASP1 isoform (called CLASP1α) has been described, whereas three CLASP2 isoforms are known (CLASP2α, -β, and -γ). Although CLASP2β/γ are enriched in neurons, suggesting isoform-specific functions, it has been proposed that during neurite outgrowth CLASP1 and -2 act in a redundant fashion by modulating MT dynamics downstream of glycogen synthase kinase 3 (GSK3). Here, we show that in differentiating N1E-115 neuroblastoma cells CLASP1 and CLASP2 differ in their accumulation at MT plus-ends and display different sensitivity to GSK3-mediated phosphorylation, and hence regulation. More specifically, western blot (WB) analysis suggests that pharmacological inhibition of GSK3 affects CLASP2 but not CLASP1 phosphorylation and fluorescence-based microscopy data show that GSK3 inhibition leads to an increase in the number of CLASP2-decorated MT ends, as well as to increased CLASP2 staining of individual MT ends, whereas a reduction in the number of CLASP1-decorated ends is observed. Thus, in N1E-115 cells CLASP2 appears to be a prominent target of GSK3 while CLASP1 is less sensitive. Surprisingly, knockdown of either CLASP causes phosphorylation of GSK3, pointing to the existence of feedback loops between CLASPs and GSK3. In addition, CLASP2 depletion also leads to the activation of protein kinase C (PKC). We found that these differences correlate with opposite functions of CLASP1 and CLASP2 during neuronal differentiation, i.e., CLASP1 stimulates neurite extension, whereas CLASP2 inhibits it. Consistent with knockdown results in N1E-115 cells, primary Clasp2 knockout (KO) neurons exhibit early accelerated neurite and axon outgrowth, showing longer axons than control neurons. We propose a model in which neurite outgrowth is fine-tuned by differentially posttranslationally modified isoforms of CLASPs acting at distinct intracellular locations, thereby targeting MT stabilizing activities of the CLASPs and controlling feedback signaling towards upstream kinases. In summary, our findings provide new insight into the roles of neuronal CLASPs, which emerge as regulators acting in different signaling pathways and locally modulating MT behavior during neurite/axon outgrowth.